Basic Studies on the Oxidative Stress Markers in Two Types of Horse Breed: Semi-isolated Population of Huculs Is Different from Commercially Used Arabian Horses - Bażanów, Barbara A. (Biomed Res Int, 2020)
Hucul and Arabian horses differ in the physiological constitution and exposition to environmental conditions. Oxidative stress plays a pathogenic role in many diseases and enables further injuries. The objective of this study was to compare the levels of enzymatic and nonenzymatic oxidative stress markers in Hucul horses living in seminatural conditions and in commercially handled Arabian horses. We tested the serum samples for total superoxide dismutase (total SOD), Cu-Zn-superoxide dismutase (CuZnSOD), and Mn-dependent superoxide dismutase (MnSOD) activity; for lipofuscin (LPS), ceruloplasmin (CER) and malondialdehyde (MDA) concentration; and for total antioxidant capacity (TAC) and total oxidant status (TOS). Total SOD (p < 0.001), MnSOD (p < 0.001), and CuZnSOD (p < 0.001) activities were significantly higher whereas LPS (p < 0.05), TAC (p < 0.001), TOS (p < 0.001), and MDA (p < 0.001) concentrations were significantly lower in the serum samples collected from Huculs vs. Arabian horses, regardless of the gender. Gender, regardless of the breed, had no significant impact on the antioxidants' activity and concentration. Total SOD and MnSOD activities were significantly higher in Hucul's mares when compared to Hucul's stallions. Concentrations of TAC and TOS were significantly lower in Arabian stallions than in Arabian mares. Commercially handled horses expressed a higher level of oxidative stress markers in comparison to breeds living in seminatural conditions. We conclude that antioxidants are important biomarkers of animal health, whether they are under maintenance care or performing physical exercise.